Iqropolly: Model Efektivitas Pembelajaran Pendidikan Agama Islam di Kampung Adat Urug, Kabupaten Bogor - Agung Suharyana; Rasi Tamadhika Fajar Ramadhan; Muhamad Yusuf; Rosyid Amrulloh; Novan Aji Imron; Lindawati Kartika; Rico Juni Artanto (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2016)
Urug Traditional Village which is located at Sukajaya Subdistrict in Bogor regency have a significant problem according to lack of religion education specifically for early age school group. The majority religion at Urug Traditional Village are moslem but their activities related to religion and social are still very limited and less interactive. For instance the religious activities like reading and learning Holy Quran is only held in one house and not at the mosque. Therefore it is very important to give an insight about the real value of Islam Religion for children in Urug Traditional Village through  educative game namely Iqropolly. The purpose of this program are: creating the Islamic atmosphere in Urug Traditional Village, Implementing the fun and religious activities and building social-interactive environtment for children specifically at Kiarapandak 02 elementary school. 3ME-N including learning, understanding, implementing and fun methode has been used in Iqropolly edugames also combines with playing and learning activities. Iqropolly has been one of  inovative edugames to stimulate the players, thus they can interact very well with others players. It also user friendly  for the players to internalize about  the islamic values and build a good character. According to the program evaluation after 4 (four) months the results showed that the children participants of this program is very responsive to the game Iqropolly. Learning outcomes of this program has reached until 78.4% in terms of good attitudes, reading Iqro, the practice of moslem praying, daily dua, reciting holy quran and knowledge about Islam. In addition, the iqropolly edugames has been proposed to obtain a patent and already published Iqropolly edugames guidance book with ISBN number.